The Effectiveness of Using Syntax Games in Fostering Students' Ability to Learn English: Perspectives from EFL Teachers - Harahap, Anggi Handayani; Daulay, Sholihatul Hamidah; Kembaren, Farida Repelita Waty (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
The primary aim of this study was to explore the effectiveness of using syntax games in fostering students' ability to learn English from the viewpoints of EFL teachers working in a private Islamic junior high school in Padangsidimpuan. The study's findings and the data gathered from a questionnaire showed that the EFL teachers have a variety of ideas about using games to teach grammar that are comparable to those discussed in the current literature. According to the study, although the EFL teachers acknowledge that games are a useful tool for teaching grammar, they do not employ games as frequently as one might anticipate in their classrooms.